Phytochemical composition, anti-inflammatory activity and cytotoxic effects of essential oils from three Pinus spp. (1st January 2017) - Basholli-Salihu, Mimoza; Schuster, Roswitha; Hajdari, Avni; Mulla, Dafina; Viernstein, Helmut; Mustafa, Behxhet; Mueller, Monika
Abstract: Context: Inflammation and cell differentiation lead to a number of severe diseases. In the recent years, various studies focused on the anti-inflammatory and anticancer activity of essential oils (EOs) of numerous plants, including different Pinus species. Objective: The phytochemical composition, anti-inflammatory and cytotoxic activity of EOs from needles and twigs of Pinus heldreichii Christ (Pinaceae) and P. peuce Griseb., and from needles, twigs and cones of P. mugo Turra were determined. Materials and methods: For separation and identification of the EOs, gas chromatography/flame ion detector (GC/FID) and GC/mass spectrometry were performed. The amount of secreted IL-6 in a lipopolysaccharide (LPS)-stimulated macrophage model was quantified (concentration of oils: 0.0001–0.2%, 3 h incubation). Cytotoxicity on the cancer cell lines HeLa, CaCo-2 and MCF-7 were determined using a MTT (Thiazolyl Blue Tetrazolium Bromide) assay (concentration of oils: 0.001–0.1%, 24 h incubation). Results: The most prominent members in the oils include: δ-3-carene, α-pinene and linalool-acetate ( P. mugo ); α-pinene, β-phellandrene and β-pinene ( P. peuce ); limonene, α-pinene and (E)-caryophyllene ( P. heldreichii ). EOs showed significant cytotoxic effects on cancer cell lines (IC50 0.007 to >0.1%), with a reduction in cell viability with up to 90% at a concentration of 0.1%, and anti-inflammatory activity (IC50 0.0008–0.02%) with a reduction of IL-6 secretion with up to 60% at a concentration of 0.01%. Discussion and conclusion: The EOs of needles and twigs from P. peuce and P. heldreichii as well as of needles, twigs and cones of P. mugo can be considered as promising agents for anticancer and anti-inflammatory drugs.